The Relationship Between Knowledge and Compliance with Occupational Safety and Health Implementation Among Nursing Profession Student - Andi Nur Suci Wulandari; Joanggi Wiriatarina Harianto; Milkhatun Milkhatun (International Journal Of Health Science, 2026)
Occupational Safety and Health in Hospitals (K3RS) is an important effort in creating a safe working environment for health workers, including nursing students undergoing clinical practice. The high risk of workplace accidents highlights the importance of compliance with K3 implementation, which is influenced by, among other things, the level of knowledge. Objective: This study aims to analyze the relationship between knowledge and compliance with Occupational Safety and Health (OS H) implementation among nursing students at Muhammadiyah University of East Kalimantan. Method: This study used a quantitative method with a descriptive analytical design through a cross-sectional approach. The research sample consisted of 145 second-semester nursing students at Muhammadiyah University of East Kalimantan, selected using total sampling technique. The research instrument was a questionnaire on OSH knowledge and compliance that had been tested for validity and reliability. Data analysis was performed using Spearman’s rank correlation test. Results: The analysis results showed a significant value of p = 0.000 (p < 0.05) with correlation coefficient of r = 0.558, indicating a significant and strong relationship between knowledge and compliance with OSH among nursing students. Conclusion: There is a significant relationship between knowledge and compliance with occupational safety and health (OSH) among nursing students. Increasing students’ knowledge is expected to improve compliance with OSH during clinical practice.